Effects of Sm3+ ions on the structural, optical and thermoluminescence properties of MnKB glass system. (February 2022) - Bhatia, Vijeta; Kumar, Dinesh; Singh, Harpreet; Kaur, Navjeet; Rao, S.M.; Kumar, Ashok; Mehta, Vimal; Singh, Supreet Pal
Abstract: In this study, the optical, thermoluminescent, structural, and physical characteristics of samarium doped manganese potassium borate glasses were analyzed using diffuse reflectance spectroscopy, thermoluminescence (TL), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy techniques. The glasses were obtained using the well-known melt–quenching process. The XRD patterns confirmed the non-crystalline characteristics of the prepared glasses and numerous structural groups were identified in the glasses based on the FTIR spectra. Physical and optical parameters were evaluated to study their responses to different Sm 3+ concentrations. The indirect and direct band gaps were evaluated based on the Tauc's plots. The TL glow curves for the glasses were analyzed after irradiation with different gamma ray doses (10 Gy–10 kGy). Kinetic parameters including the frequency factor and activation energy were determined using the peak shape method. Highlights: Structural, optical, and thermoluminescence properties of Sm 3+ doped MnKB glasses investigated. Amorphous nature of glass samples confirmed by powdered XRD. Interesting features identified by structure and FTIR studies, such as conversion of BO3 to BO4 structural units and vice versa. Band gap calculated using K-M function tended to increase with the Sm 3+ ion concentration. Single TL glow peak observed for all glass samples with different Sm2 O3 concentrations.